2010
DOI: 10.1016/j.jcin.2010.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Occlusion of Patent Ductus Arteriosus in Pre-Term Infants

Abstract: It is technically feasible to undertake transcatheter coil closure of PDA in carefully selected symptomatic pre-term infants, and it is a safe alternative to surgical ligation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(81 citation statements)
references
References 14 publications
1
76
0
4
Order By: Relevance
“…More recently, Baspinar et al reported similar success rate of 94.3% in 53 infants under 6 kg but a lower success rate of 81.2% in 16 premature infants weighing <2.5 kg and one procedure related death in this group. The feasibility of transcatheter closure in premature infants <2.5 kg has also been reported in a handful of case series with the smallest patient weighing 645 g having an uncomplicated closure with a 5 mm coil .…”
Section: Discussionmentioning
confidence: 86%
“…More recently, Baspinar et al reported similar success rate of 94.3% in 53 infants under 6 kg but a lower success rate of 81.2% in 16 premature infants weighing <2.5 kg and one procedure related death in this group. The feasibility of transcatheter closure in premature infants <2.5 kg has also been reported in a handful of case series with the smallest patient weighing 645 g having an uncomplicated closure with a 5 mm coil .…”
Section: Discussionmentioning
confidence: 86%
“…Depending on the size and shape of PDA, various types of devices have been used in transcatheter closure of PDA. For most children and adult with PDA, safe and effective transcatheter closure of PDA has been achieved with ADO2,5,14,15). Also, varying sizes of PDA had been occluded with the use of single or multiple coils3,16).…”
Section: Discussionmentioning
confidence: 99%
“…Delayed closure of the hemodynamically significant patent ductus arteriosus is related to the development of various morbidity in preterm infants21). Transcatheter closure of PDA can be considered as treatment option to avoid the risk of surgical ligation in these patients22).…”
Section: Discussionmentioning
confidence: 99%